Dark Age Bodies: Gender and Monastic Practice in the Early Medieval West. By Lynda L. Coon - White, Carolinne (The journal of theological studies, 2011)
This beautifully presented book offers the reader seven chapters on various figures and products of Carolingian monastic culture, focusing particularly on the life and achievements of Hrabanus Maurus and his predecessors as abbot of Fulda, the pictures and versus intexti in Hrabanus Maurus’ series of carmina figurata entitled In honour of the Holy Cross, the architecture of the monastery at Fulda, and the wonderfully detailed Plan of St Gall. These subjects are set against the background of the Benedictine Rule and in particular the rich ninth-century commentaries on the Rule by Smaragdus of Saint-Mihiel and Hildemar of Corbie.